Application of Virtual Reality and Plant Modeling for Participation in Urban Planning and Design - Lim, Enmi; Umeki, Kiyoshi; Honjo, Tsuyoshi (International Journal of Virtual Reality, 2009)
In landscape planning, visualization of landscape is a powerful tool for public understanding and for selection of alternative plans. In recent years, three dimensional (3D) computer graphics (CG) were used as visualization tools of environment because it has the ability to accurately simulate the changes caused by a proposed plan. In particular, virtual reality (VR), which enables to walk through in a modeled park or in a visualized forest, was considered as the advanced technique of landscape visualization. In this study, we developed a landscape visualization system with graphic user interface, which we named VR-Terrain (GUI version), to generate the virtual reality image easily by using VRML (Virtual Reality Modeling Language) and plant modeling techniques. In order to test the feasibility of the landscape visualization system, we applied the system to Ichinoe Urban Design Plan. Ichinoe is located at Edogawa Ward, Tokyo. There is a Sakaikawa Shinsui Park with water space surrounded by large amount of green. In the case study, we simulated the landscape of Sakaikawa Shinsui Park with about 200 plants and 300 buildings. We used the images simulated by VR-Terrain to explain the concept (such as building height limit) to the residents in the public meetings. It took about 30 hours to make the 3D model of the town. After ten minutes of training, anybody can walk through in the simulated town freely. The results showed that the VR image by the system helped the public understanding of the concept of the urban plan.